After the Fall : Lessons for Policy Cooperation from the Global Crisis - Bayoumi, Tamim (Washington, D.C. : International Monetary Fund, 2014)
A crisis is a terrible thing to waste, and nowhere is this truer than in the arena of international economic policy cooperation. With the world facing the largest and most synchronized plunge in output of the postwar era, policy makers banded together to find solutions. This paper looks at the lessons from what did-and did not-occur in the area of policy cooperation since the crisis. Outcomes seem to be weaker over time in areas such as macroeconomic policies, where institutional procedures were less well defined and there were disagreements over spillovers. By contrast, cooperation seems to have been most effective where there was a consensus that such policies could avoid the risk of highly detrimental outcomes and institutional arrangements were more concrete. Principle amongst these was trade, but bank capital buffers, IMF resources, and derivatives exchanges also fall into this category. Lessons for those interested in promoting cooperation seems to be: it may be more fruitful to: focus on the potential for major costs from a lack of cooperation, rather than the minor gains from fuller coordination; strive for more consensus estimated spillovers; convince policy-makers costs of loss of cooperation are large; and focus on building better and more enduring institutional arrangements.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet